Pengaruh Tiktok Shop, Uang Saku Dan Literasi Keuangan Terhadap Perilaku Konsumtif Pengguna Aplikasi Tiktok Pada Mahasiswa Fakultas Keguruan Dan Ilmu Pendidikan Universitas Islam Riau - Maimunah, Siti; Suryanti, Nunuk (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to find out whether TikTok shop, pocket money, and financial literacy influence the consumptive behavior of TikTok application users among students at the Faculty of Teacher Training and Education, Riau Islamic University. This research quantitative descriptive research methods using SPSS version 12 software. Data collection was carried out through questionnaires distributed to 358 respondents, which were obtained using the slovin formula of approximately 3333 student populations at the Faculty of Teacher Training and Education, Riau Islamic University. The main data comes from a questionnaire with data analysis techniques, namely the classic assumtion test consisting of the normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing, namely the multiple linear regression test, t test, f test and coefficient of determination test. The researchiresults showithat TikTok Shop has a influenceion consumptive behavior of TikTok application users. Pocket money influences the consumptive behavior of TikTok application users.. Financial literacy influences consumptive behavior of TikTok application users. TikTok Shop (X1), pocket money (X2), and financial literacy (X3) simultaneously have a significant effect on consumptive behavior (Y) of TikTok application users.